Interior design for libraries drawing on function & appeal - Brown, Carol R.; ebrary, Inc. (Chicago : American Library Association, 2002)
"If you are competing for customers with the bookstore down the street that serves up lattes and comfy chairs, then you know that the look and feel of your library can make a difference when it comes to bringing in people of all ages. Focusing on functionality (for staff) and appeal (for customers), this illustrated how-to guide offers a comprehensive plan for designing new or renovated spaces." "With 15 color plates and 25 halftones that illustrate how different elements work together to form an overall design, this must-have book will help you turn any type of library into a welcoming and efficient space for customers young and old."--BOOK JACKET.
Includes bibliographical references (p. 137-138) and index.
Electronic reproduction.
Keywords: Library buildings -- United States -- Design and construction; Library decoration; Library fittings and supplies; Electronic books